Keraton Indonesia Antara Pelestarian Budaya Dan Modernitas - Anak Agung Ngurah Agung Wira Bima Wikrama (Jurnal Ilmiah Cakrawarti, 2020)
The palace as a traditional cultural heritage of Indonesia experiences cultural tensionalong with the occurrence of modernity in Indonesia. Modernization has marginalized the role andfunction of the Palace as the center of traditional power. Conversely, efforts to build the existence ofthe Palace can be questioned about its relevance or merely cultural romance. For this reason, thisstudy examines three main problems. First, why does the Keraton preserve the Keraton Culture inIndonesia? Second, how are the forms of preservation of Keraton Culture in Indonesia? Third, whatare the implications of the Keraton Cultural Preservation in Indonesia? These three problems areexamined with three theories, namely the theory of social change, cultural adaptation, and geneticstructuralism. The research method used is qualitative research with three data collection techniques,namely observation, interviews, and document studies. Data were analyzed with descriptiveinterpretativetechniques through three stages, namely data reduction, data presentation, and drawingconclusions. The results show that the reasons underlying the preservation of the Keraton Culture in Indonesia include rebuilding the existence of the Palace, maintaining the status quo, structuraldifferentiation, and the charm of modern life. The forms of preservation of Keraton Culture include(1) passive preservation, namely the construction of the physical structure of Keratondan andmaintaining the attributes of royal identity; (2) active preservation, i.e. optimizing capital owned bythe Palace with specific patterns and specific goals in the structure of modern society; and (3)Keraton network preservation, namely strengthening collegial collective systems and networkexpansion. Implications of Keraton Cultural Preservation in social life include reformulation ofsocial relations and shifting the patron-client system. The implication in cultural life is in the form ofstrengthening Keratonsas cultural heritage and strengthening Keratonsas the center of culturaldevelopment.